Patient Transfer Process From Pre‐Hospital to the Hospital Emergency Department: A Grounded Theory Study - Maryam Jamsahar; Fazlollah Ahmadi; Mitra Khoobi; Mojtaba Vaismoradi (Nursing Open, 2025)
ABSTRACT Background The transfer of patients from a pre‐hospital emergency environment to a qualified healthcare centre is a critical aspect of emergency care. Due to the unpredictable and uncontrolled nature of pre‐hospital environments, emergency care providers often encounter multiple challenges during the patient transfer process. Aim/Objective This study aimed to explore the patient transfer process from pre‐hospital to the hospital emergency department, identify the areas of main concern, strategies that emergency care providers used to address these concerns and generate a coherent underlying theory. Methods A qualitative research method using a grounded theory approach was carried out to develop a comprehensive theoretical framework based on the experiences of emergency care providers, patients and their relatives in pre‐hospital settings and hospital emergency departments. This study, conducted from September 2022 to January 2024, involved 24 participants: 18 emergency care providers, four patients' relatives and two patients with transfer experience. Sampling began purposefully and transitioned to theoretical sampling to ensure diversity and enrich the emerging theory. Data were collected through in‐depth, individual, semi‐structured interviews, along with note‐taking, observation and document review. The Corbin‐Strauss 5‐step analysis approach was used to develop a coherent theory capturing the essence of the study phenomenon. The steps included open coding to identify concepts, developing concepts based on their features and dimensions, analysing data for context, incorporating processes into the analysis and integrating categories. Results The main category as the main concern of the participants was ‘the tension of delay in safe transfer and patient survival threat’. The central variable was ‘diligent avoidance of tense confrontation’, which was used as a conscious, deliberate and purposeful effort to prevent the escalation of tensions in various situations and included a set of different strategies such as situational resourcefulness, persuasive communication and forbearance. Ultimately, the emergency care providers' efforts caused different outcomes, from successful persuasion and safe transfer of the patient to unsuccessful persuasion, surrendering, escaping from responsibility and long‐lasting hidden tensions. Conclusions Emergency care providers use different strategies to manage the tension of delay in safe transfer and patient survival threat as their main concern. While successful strategies can inform practical guidelines, negative consequences highlight the need for more efficient and effective approaches. A prescriptive model based on the contextual theory from this study can be designed. This model should take a comprehensive, multifaceted view of the underlying causes of tension, support emergency care providers and improve their experience of delays during patient transfers in pre‐hospital emergency settings, ultimately leading to safe care. Implications for the Profession and/or Patient Care Emergency care providers should balance the urgency of transfer with patient safety and the patient's relative concerns. Impact This study underscores the need for patient‐centred care, effective communication and practical strategies to improve patient transfer processes. Reporting Method This article has been presented based on the COnsolidated Criteria for REporting Qualitative Research (COREQ) checklist. Patient or Public Contribution No Patient or Public Contribution.